The lieutenant's bargain [large type] - Jennings, Regina (Regina Lea) (Jennings, Regina (Regina Lea). Fort Reno series., 2019)
Hattie Walker dreams of becoming a painter, while her parents want her to settle down. As a compromise, they give her two months to head to Denver and place her works in an exhibition or give up the dream forever. Her journey is derailed when a gunman attacks her stagecoach, leaving her to be rescued by a group of Arapaho . . . but she's too terrified to recognize them as friendly. Confirmed bachelor Lieutenant Jack Hennessey has long worked with the tribe and is tasked with trying to convince them that the mission school at Fort Reno can help their children. When a message arrives about a recovered survivor, Jack heads out to take her home--and plead his case once more. He's stunned to run into Hattie Walker, the girl who shattered his heart--but quickly realizes he has a chance to impress her. When his plan gets tangled through translation, Jack and Hattie end up in a mess that puts her dreams in peril--and tests Jack's resolve to remain single.